Efforts to Improve Mathematics Learning Outcomes in Grade 2 at SD Negeri 2 Gaden through the Use of Concrete Media - Hartini, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to enhance mathematics learning outcomes in grade 2 at SD Negeri 2 Gaden through the use of concrete media. The research method employed is classroom action research, implementing a teaching strategy involving concrete media such as math manipulatives and educational games. The results indicate that the application of concrete media significantly improves student participation, deepens the understanding of mathematical concepts, and fosters a more positive learning environment. This improvement is observable through the comparison of learning outcomes before and after the implementation of concrete media. These findings offer practical recommendations for teachers and schools to consider the use of concrete media in efforts to improve mathematics learning outcomes in grade 2 at SD